Association of Serum Retinol Concentrations With Metabolic Syndrome Components in Iranian Children and Adolescents: The CASPIAN-V Study - Qorbani, Mostafa; Seif, Ehsan; Heshmat, Ramin; Ghonbalani, Zahra Nouri; Basiry, Pouria; Kazemian, Elham; Kelishadi, Roya (Frontiers in Nutrition, 2022)
Background: As a fat-soluble vitamin, vitamin A plays a crucial role in adipogenesis, lipolysis, insulin resistance, and obesity. However, it is still unclear whether they are associated with cardiometabolic risk factors in children and adolescents. The current study aimed to determine the association between serum retinol concentration and the cluster of metabolic syndrome components among children and adolescents. Methods: This nationwide cross-sectional study was performed on 2518 students aged 7–18 years from the Childhood and Adolescence Surveillance and Prevention of Adult Non- communicable disease (CASPIAN-V) study. Students were selected via multistage cluster sampling method from 30 provinces of Iran in 2015. Multivariable logistic regression was used to assess the association of serum retinol concentration with metabolic syndrome (MetS) components. Results: Overall, the mean (SD) age of study participants was 12.16 (3.04) years, and 44.9% (n = 1,166) of them were girls. The mean serum retinol concentration was 1.48 ± 1.55 µmol/L and vitamin A deficiency was observed among 19.7% (95% CI: 18.2-21.3) of study subjects. The results of the logistic regression analysis showed that increasing serum retinol concentrations were associated with an increased likelihood of developing obesity (OR: 1.12, 95% CI: 1.04, 1.20), abdominal obesity (OR: 1.07, 95% CI: 1.01, 1.14), low high-density lipoprotein cholesterol (HDL-C) (OR: 1.10, 95% CI: 1.04, 1.16) and high fasting blood glucose (FBG) (OR: 1.21, 95% CI: 1.10, 1.35), whereas it was associated with a decreased odds of developing high blood pressure (OR: 0.82, 95% CI: 0.73, 0.93). Nevertheless, there was no statistically significant association between metabolic syndrome itself and retinol concentration (OR: 1.02, 95% CI: 0.88, 1.18). Conclusion: We found that serum retinol concentration was positively associated with metabolic syndrome components such as obesity, low HDL-C, and high FBG, but not with metabolic syndrome itself.